The effect of mineralogy and microfabric on the shear strength of clayey from the Trusmardi formation in Bundu Tuhan, Sabah - Khairul, Nur Ayu Sufiah; Erfen, Hennie Fitria W. S.; Musta, Baba (Science, Engineering and Health Studies, 2025)
Soil instability, including slope failure and creeping, frequently occurs in the research area of Bundu Tuhan, Sabah. The lithology in this region primarily comprises interbedded sandstone, metasandstone, shale, and argillite from the Trusmadi formation. Intense weathering contributes to the formation of thick, clayey soil profiles. Geotechnical laboratory tests classified clayey soils from three distinct locations as poorly sorted materials of sandy-silty clay and silty clay textures. X-ray diffractograms revealed the presence of kaolinite and illite in the clayey soils. Electron microscopy images demonstrated the microfabric characteristics of clayey soil, such as pseudohexagonal plate shapes of kaolinite and ribbon-like projections of illite. Shear strength analysis results of the clayey soil samples indicated values ranging from 128.28 to 155.01 kPa, classifying the soils as strong. The presence of clay minerals in the soil facilitated water adsorption into the mineral structure, potentially softening the soil and reducing its shear strength. Understanding the mineralogical composition of these soils is essential for mitigating soil instability by implementing measures like lime treatment on slopes, particularly in high-risk areas.